2009
DOI: 10.1177/0269881108100256
|View full text |Cite
|
Sign up to set email alerts
|

Review: Nicotinic receptors and stages of nicotine dependence

Abstract: Smoking is one of the leading causes of preventable death, where nicotine has been identified as the primary addictive constituent of tobacco. Consequently, there have been extensive investigations into the neuroadaptations that occur as nicotine dependence develops, where numerous neurological systems have been implicated. The focus of this review was on nicotinic acetylcholine receptor neuroadaptations that occur during the development of nicotine dependence. This focus was selected because (1) the nicotinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 178 publications
(221 reference statements)
0
28
0
1
Order By: Relevance
“…As aforementioned, Yu et al (2010) found no enhancing effect of nicotine (0.15 or 0.5 mg/kg, subcutaneously) in mice that had been prenatally exposed to maternal infectious agents. However, a single injection of nicotine was administered to model an acute effect as opposed to repeated nicotine treatment, which leads to different neurochemical alterations (Brennan et al, 2010), and therefore might affect cognitive performance differently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As aforementioned, Yu et al (2010) found no enhancing effect of nicotine (0.15 or 0.5 mg/kg, subcutaneously) in mice that had been prenatally exposed to maternal infectious agents. However, a single injection of nicotine was administered to model an acute effect as opposed to repeated nicotine treatment, which leads to different neurochemical alterations (Brennan et al, 2010), and therefore might affect cognitive performance differently.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the cholinergic system and nAChRs in mediating cognitive processes has been observed across multiple species (Klinkenberg et al, 2011; Wallace and Porter, 2011; Rezvani and Levin, 2001), and improvements in humans have been shown in domains relevant to schizophrenia, such as sensorimotor gating (Postma et al, 2006; Woznica et al, 2009), attention (Barr et al, 2008; Hahn et al, 2012), memory (Jubelt et al, 2008) and executive control (Petrovsky et al, 2013). Neuronal α7 receptors, for example, exist at pre- and post-synaptic locations; thus, they can rapidly mediate synaptic transmission and plasticity, as well as neurotransmitter release that is relevant to cognitive functioning, such as that of acetylcholine, dopamine, glutamate, serotonin and GABA (Benowitz, 2009; Brennan et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…With increasing research suggesting potential roles of other nAChRs subtypes in nicotine addiction (e.g. β3, β4, α4 and α6) (see Brennan et al 2010;Penton and Lester 2009 for reviews), it is important that future research begins to determine the extent to which these receptors may also be involved in the nicotine-induced impulsivity. Figure 1 clearly shows a gradual strengthening (i.e.…”
Section: Effects Of Chronic Nicotinementioning
confidence: 99%
“…As discussed above, chronic exposure to nicotine in tobacco alters nAChR levels in the human brain, and this may contribute to the development of nicotine dependence (Staley et al 2006). A large number of studies have identified the nAChR subtypes, and critical brain circuits responsible for the addictive effects of nicotine, in particular, the ability of nAChRs in the ventral tegmental area to drive dopamine release and support nicotine reinforcement (reviewed in: Brennan et al 2010; Buisson and Bertrand 2002; Changeux 2010; Govind et al 2009). Nicotine dependence is also co-morbid with other substance abuse disorders, including addiction to cocaine, alcohol, cannabinoids, and opiates (Tuesta et al 2011).…”
Section: Evidence For Nachr Expression or Trafficking Abnormalities Imentioning
confidence: 99%